LINGUISTIC AXIOLOGY: ITS FEATURES AND INTERDISCIPLINARY RELATIONS - Burxonova Mohira Omonilla qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
Linguistic axiology, as a subfield of linguistics, explores the value-laden nature of language and its ability to encode ethical, cultural, and emotional meanings. Drawing upon global research from cognitive linguistics, translation theory, and ethnolinguistics, this article outlines the foundational features of linguistic axiology and its integration with other disciplines. The study synthesizes international perspectives to highlight how language operates as a medium for value transmission across diverse cultural and academic landscapes.